Early high flow nasal cannula therapy in bronchiolitis, a prospective randomised control trial (protocol): A Paediatric Acute Respiratory Intervention Study (PARIS). Issue 1 (December 2015) - Franklin, Donna; Dalziel, Stuart; Schlapbach, Luregn; Babl, Franz; Oakley, Ed; Craig, Simon; Furyk, Jeremy; Neutze, Jocelyn; Sinn, Kam; Whitty, Jennifer; Gibbons, Kristen; Fraser, John; et al.
Abstract Background Bronchiolitis imposes the largest health care burden on non-elective paediatric hospital admissions worldwide, with up to 15 % of cases requiring admission to intensive care. A number of previous studies have failed to show benefit of pharmaceutical treatment in respect to length of stay, reduction in PICU admission rates or intubation frequency. The early use of non-invasive respiratory support devices in less intensive scenarios to facilitate earlier respiratory support may have an impact on outcome by avoiding progression of the disease process. High Flow Nasal Cannula (HFNC) therapy has emerged as a new method to provide humidified air flow to deliver a non-invasive form of positive pressure support with titratable oxygen fraction. There is a lack of high-grade evidence on use of HFNC therapy in bronchiolitis. Methods/Design Prospective multi-centre randomised trial comparing standard treatment (standard subnasal oxygen) and High Flow Nasal Cannula therapy in infants with bronchiolitis admitted to 17 hospitals emergency departments and wards in Australia and New Zealand, including 12 non-tertiary regional/metropolitan and 5 tertiary centres. The primary outcome is treatment failure; defined as meeting three out of four pre-specified failure criteria requiring escalation of treatment or higher level of care; i) heart rate remains unchanged or increased compared to admission/enrolment observations, ii) respiratory rate remains unchanged or increased compared to admission/enrolment observations, iii) oxygen requirement in HFNC therapy arm exceeds FiO2  ≥ 40 % to maintain SpO2  ≥ 92 % (or ≥94 %) or oxygen requirement in standard subnasal oxygen therapy arm exceeds >2L/min to maintain SpO2  ≥ 92 % (or ≥94 %), and iv) hospital internal Early Warning Tool calls for medical review and escalation of care. Secondary outcomes include transfer to tertiary institution, admission to intensive care, length of stay, length of oxygen treatment, need for non-invasive/invasive ventilation, intubation, adverse events, and cost. Discussion This large multicenter randomised trial will allow the definitive assessment of the efficacy of HFNC therapy as compared to standard subnasal oxygen in the treatment of bronchiolitis. Trial registration The trial is registered with the Australian and New Zealand Clinical Trials RegistryACTRN12613000388718 (registered on 10 April 2013).